Evaluasi Kinerja Keuangan Perusahaan Perbankan: Studi Kasus Analisis Rasio Keuangan Periode 2020-2022 - Firdausii Khoirunnisa; Yanda Bara Kusuma (Jurnal Akuntan Publik, 2024)
This research explores the evaluation of financial performance in banking companies through financial ratio analysis and case studies. Analyzing three banks – BNI, BRI, and Bank Mandiri – reveals variations in stock prices, financial efficiency, and net profit performance. The conclusion is that BNI's stock is undervalued, BRI's is overvalued, and Bank Mandiri's situation is mixed. Although debt ratios are safe, both ROA and ROE fall below standards. However, operational efficiency is reflected in a healthy NPM. This study provides in-depth insights into the complexity of banking companies' performance.